Empowering Class IX Students' Moral Values: The Vital Role of a Catholic Religion Teacher (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
This study aimed to describe the role of Catholic religious education teachers in increasing the moral values of class IX students at SMP Swasta Katolik 2 Kabanjahe. The problem in this study is that there are still teachers who do not fully understand their role in increasing the moral values of students, so the moral values of students quickly decline due to the times. This study uses a descriptive-qualitative approach. Research data was obtained through observation, interviews, and documentation. The informant determination technique used was snowball sampling. The informants in this study consisted of 1 school principal, 1 Catholic Religious Education teacher, 7 colleagues, and 10 students. The data analysis technique uses technical triangulation: reduction, display, and concluding. The study results show that Catholic religious teachers have carried out their duties as well as possible, namely carrying out their roles as role models, educators, and pastors. Meanwhile, students also have good moral values, namely being religious, honest, responsible, disciplined, and independent. The results of this study can be used in other places if the places have characteristics that are not much different from the ones found in the research that has been done. This research is limited to the role of Catholic religious education teachers and the moral values of students.